Estudo do comportamento viscoelástico de concretos asfálticos convencionais e modificados através de ensaios de laboratório e de análise de desempenho - Bruxel, Daiana Frank (2015)
Road transport is of great importance for many countries, in Brazil it can be even more extreme, by excessive movement of cargo through this modal. We know that the maintenance costs of roads are high, forcing researchers to find always new alternatives to improve the use of materials, reduce energy consumption, speed up restoration interventions, among others. The goal of this study is to evaluate the behavior of conventional asphalt mixtures of polymers and modified for resistance and deformability. For this study, we used a crushed mineral aggregate skeleton of volcanic origin with framed particle size in the range of C DNIT, coming from the quarry of Santo Antonio da Patrulha RS. 4 types of asphalt binders were used, the CAP 50/70, the TLA CAP, the CAP 60/85 and the TLA FLEX, and the latter two are modified polymers. Compression was done according to Superpave methodology. Tests were carried out to check the mechanical behavior (test Tensile Strength for Diametral Compression (RT) assay Resilience Module (MR) and Dynamic Module test Uniaxial) and later held one performance analysis of mixtures studied by AASHTOWare software. From these investigations it was possible to verify the behavior of the mixtures studied for their resistance, deformability and especially as its durability. It can be said that the choice of the mixture to be used will depend on its applicability. The tests showed that mixtures with TLA Flex achieved the best results, a fact that was confirmed by performance analysis that demonstrated the mixture of TLA Flex with a thickness of 18 cm coating meets all requirements evaluated.